PRODUKSI DAN CITA RASA SERTA KANDUNGAN POLIFENOL TEH KULIT MELINJO - Saragih, Raskita; Tamizi, Ermiziar (E-Journal Widya Kesehatan dan Lingkungan, 2020)
Melinjo peels waste can be processed into herbal tea. A total of 22,963 tons per year of melinjo is processed into emping and that much waste of melinjo peels is also wasted (BPS Banten 2014). Red and green melinjo peels contains polyphenols, antioxidants and amino acid L glutamate acid (Saragih, R and Ermiziar, 2019). The aim of the research was to produce herbal teas from red and green melinjo peels, test their taste and aroma and analyze total polyphenols and antioxidants. Melinjo peels tea is produced by sorting the melinjo peels, washing, cutting and drying using an oven blower. A factorial randomized block design with two factors was used. Drying temperature factor with three levels: 55, 60 and 65oC and drying time with levels 4,5 and 6 hours. indicators tested for taste and aroma, total polyphenols and antioxidants. Melinjo peels herbal tea production process is best at a drying temperature of 65oC for 4 hours. The taste and aroma of red melinjo peels tea is preferred with values ​​of 3.60 and 3.28. Green melinjo peels tea, with a value of 3.52 and 2.88 means like it too. The total content of red melinjo peels tea polyphenols is 18.34 mg / L. and antioxidants 1.54 mg / kg. Green melinjo peels tea total polyphenols 4.87 mg / L and antioxidants 1.63 mg / kg. Red and green melinjo peels herbal tea has the potential as an alternative healty drinks.